Rigidity, Torsion, and Mechanical Response of a Tetra-Stranded Genome : A Unified Theoretical and Experimental Framework for Q-DNA Elasticity - Barack Ndenga (Publisher, 2025)
The mechanical properties of a hereditary polymer constrain its capacity for replication, transcription, and segregation. Duplex DNA occupies a well-characterized elastic regime described by the worm-like chain (WLC) and its twistable extensions. Here, I develop a unified theoretical and experimental framework for the mechanics of Q-DNA, a canonical tetra-stranded hereditary polymer, and show that such a system necessarily defines a distinct elastic regime. I introduce a generalized worm-like chain model (Q-WLC) incorporating multi-strand bending, torsion, and inter-strand coupling modes, derive experimentally observable response functions, and propose concrete single-molecule assays capable of validating or falsifying the model. This work establishes mechanics as a decisive feasibility axis for tetra-stranded heredity. Keywords: Q-DNA, tetra-stranded genome, worm-like chain, twistable WLC, single-molecule force spectroscopy, torsional stiffness
The mechanical properties of a genetic polymer impose fundamental constraints on its ability to support replication, transcription, and long-term heredity. Duplex DNA occupies a well-characterized elastic regime described by the worm-like chain (WLC) model and its twistable and extensible variants, with quantitative benchmarks established through single-molecule force and torque spectroscopy. In this work, I develop a unified theoretical and experimental framework for the mechanics of Q-DNA, defined as a canonical tetra-stranded hereditary polymer. I show that genome-scale tetra-strand coupling necessarily gives rise to a distinct elastic regime, which cannot be reduced to a simple perturbation of duplex DNA mechanics. I introduce a generalized worm-like chain model (Q-WLC) that incorporates multi-strand bending, torsion, and internal strand-registry modes. This framework predicts modified force–extension behavior, altered twist–stretch coupling, and the emergence of multi-step mechanical transitions associated with internal strand rearrangements rather than duplex-like denaturation. These predictions are explicitly formulated to be falsifiable using existing single-molecule platforms, including optical and magnetic tweezers. By linking_translation-level mechanical observables to the feasibility of replication and transcription, this work establishes mechanics as a decisive criterion for evaluating tetra-stranded heredity. More broadly, it positions Q-DNA elasticity as a testable physical hypothesis at the intersection of polymer physics, molecular biophysics, and synthetic genetics, and provides a concrete pathway for experimental validation or refutation.